DOI: 10.32657/10356/42365
|View full text |Cite
|
Sign up to set email alerts
|

The strength and deformation behaviour of a residual soil in Singapore

Abstract: The research work presented in this report was carried out under the supervision of Associate Professor Chu Jian. I would like to express the most sincere gratitude for his inspiration, patience and guidance. His endlessly support and invaluable experience came handy throughout the whole year. His close monitoring and encouragement are especially appreciated. I also extends my heartily appreciation to: The technical staff of Geotechnics labs, especially Mr. Tay Soon Leung, Mr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 106 publications
1
2
0
Order By: Relevance
“…implies an increase in pore water pressure, which in turn indicates normally consolidated (NC) behavior (Meng, 2010). This is also consistent with the effective stress paths showing in Fig.…”
Section: Direct Simple Shear (Dss) Tests On Kaolinsupporting
confidence: 87%
See 1 more Smart Citation
“…implies an increase in pore water pressure, which in turn indicates normally consolidated (NC) behavior (Meng, 2010). This is also consistent with the effective stress paths showing in Fig.…”
Section: Direct Simple Shear (Dss) Tests On Kaolinsupporting
confidence: 87%
“…8.6b. As this is an undrained test and the total σ n is maintained constant, the change in the effective vertical stress is also the change in pore water pressure (Chu et al, 1999;Chu et al, 2003;Meng, 2010). A decrease in σ n '…”
Section: Direct Simple Shear (Dss) Tests On Kaolinmentioning
confidence: 99%
“…There were several studies in the literature on the K 0 consolidation behaviour of either naturally or artificially cemented sands (Maccarini, 1987;Zhu et al, 1995;Yun and Santamarina, 2005;Meng, 2010;Yun and Evans, 2011). Zhu et al (1995) found that the coefficient of lateral earth pressure at rest K 0 reduces with the Chapter 2 Literature Review 21 increase in cement content for sand and the imposed vertical stress will induce the breakage of cementation bonding inside the soil.…”
Section: Chaptermentioning
confidence: 99%